Model Penganggaran Penyelenggaraan Pemilihan Kepala Daerah Bersumber Dari Anggaran Pendapatan Dan Belanja Negara Melalui Dana Perimbangan - Taufik Hidayat; Syarief Makhya; Tabah Maryanah (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
Regional head elections were held simultaneously on December 9, 2020, followed by 9 provinces, 224 districts and 37 cities in the territory of Indonesia. The budget for holding the simultaneous regional head elections in 2020 is sourced from a Regional Budget (APBD) grant from the Regional Government. However, the budgeting process sourced from the APBD had encountered problems, there were 3 provinces and 58 districts / cities that had not signed the Regional Grant Agreement (NPHD) even though it had passed the deadline for the NPHD preparation and signing stages, namely on October 1, 2019. Budget issues This will continue to be repeated as long as the regional head elections are still sourced from the APBD. This study aims to provide an idea of the budgeting model for regional head elections sourced from the State Budget through the Balancing Fund, namely the General Allocation Fund (DAU) and the Special Allocation Fund (DAK). This study uses a descriptive research method with a qualitative approach. The technique of collecting data through literature study. The results of this study indicate that budgeting sourced from the APBN through the balance fund will be able to accommodate the budget needs for the implementation of regional head elections, simplify complicated administration, and be free of budget political intervention in the regions. Keywords : Pilkada Budgeting Model, APBN, Balancing Fund, DAU, DAK